Which category to extend to - Product or service - ARSLAN, FATMA MÜGE (My University, 2012)
As brands have become the main asset of firms, many of them try to take advantage of their well-known brands by extending into different product categories. Most previous research on brand extensions focus on extending a physical product into new physical product categories. Although it is possible to see many examples of service brand extensions, only a limited number of studies have focused on service brand extensions. The aim of this study is to investigate whether consumer evaluations vary between physical and service brand extensions of a parent service brand and which type of extensions are more successful - service or product? The study explores four parent service brands in different industries extending into both high-fit and low-fit physical product and services categories. The study adopts Aaker and Keller's (1990) model with the minor addition of perceived risk. The findings of the study show that for parent service brands extending into a service category is evaluated more favorably. In addition to the independent variables of Aaker and Keller's (1990) model, perceived risk has also showed a significant effect on evaluation of the extension. © 2012 Macmillan Publishers Ltd.
Keywords: brand extension; diffi culty; fit; perceived quality; perceived risk; service brands